PENGARUH KELEKATAN EMOSIONAL DENGAN ORANG TUA TERHADAP REGULASI EMOSI REMAJA KELAS VII DI SMP NEGERI 2 SAKETI - Dafika Filzah Nabila; Rochani; Siti Muhibah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The quality of emotional relationships with parents is an important foundation for adolescents in developing stable emotional regulation skills. However, in reality, there are still students who experience emotional barriers such as withdrawal, difficulty socializing, and even bullying. This study aims to determine the effect of emotional attachment to parents on the emotional regulation of seventh-grade students at SMP Negeri 2 Saketi. The approach used is quantitative with a causal associative method. The population in this study consisted of 65 seventh-grade students with a sampling technique using non-probability sampling of the saturated sampling type. The results of statistical analysis through simple linear regression tests showed a significance value of 0.009 (0.009 < 0.05), which means that there is a significant and positive influence between emotional attachment to parents and emotional regulation. The coefficient of determination value shows that emotional attachment contributes 10.3% to students' emotional regulation. The results of this study indicate that the higher the level of attachment adolescents have toward their parents, the greater their emotional regulation skills. A strong emotional bond with parents provides a foundation for students to remain calm and adaptable when facing stress in the school environment.